Dampak Permainan Game Online Terhadap Perilaku Komunikasi Anak Di Lingkungan Keluarga Pada Desa Pulau Tujuh, Kecamatan Pamenang Barat, Kabupaten Merangin - Rifa Mutiara Adha; Arfan; Yuanita; Sinta Rahmatil Fadhilah; Ayu Nurhayati; Sandi Maspika; Afriansyah (Journal of Religion and Film, 2024)
research aims to analyze the impact of playing online games on children's communication behavior in the family environment in Pulau Tujuh Village, West Pamenang District, Merangin Regency, Jambi Province. The theory used in this research is George Gerbner's Cultivation Theory which states that media, including online games, can shape individual perceptions and behavior in the long term. The research method used is a quantitative method with a survey approach. The population in this study were all children in Pulau Tujuh Village who actively played online games. Sampling was carried out using a stratified random sampling technique to ensure proportional representation of various age and gender groups. Data was collected through questionnaires distributed to 84 child respondents. The research results show that playing online games has a significant impact on children's communication behavior in the family environment. Children who often play online games tend to show more closed communication behavior, are less interactive with family members, and spend more time in front of the screen than interacting directly. In addition, it was found that the intensity of playing online games was closely related to a decrease in the frequency of verbal and non-verbal communication between children and parents.